Spontaneous cholecystocutaneous fistula: still a complication of gallstones - Har, Bappaditya; Shinde, Rounak; Prasad, Abhishek; Chattopadhyay, Bitan Kumar (International Journal of Research in Medical Sciences, 2017)
Inspite of the tremendous improvement in early diagnosis and treatment of gallstones patients still present with spontaneous cholecystocutaneous fistula. With the introduction of widespread use of ultrasonography for diagnosis & laparoscopic cholecystectomy, it has now become a rare complication. Over the past 50 years fewer than 20 cases has been reported. We report here, a case presenting with discharging opening in anterior abdominal wall with intermittent expulsion of stones.